Articulating the exuberant intricacies of bacterial exopolysaccharides to purge environmental pollutants. Issue 11 (November 2021) - Mehta, Krina; Shukla, Arpit; Saraf, Meenu
Abstract: Microbial exopolysaccharide (EPS) is composed of a mixture of macromolecules such as proteins, polysaccharides, humic-like compounds, and nucleic acids, which encase microbial cells in a three-dimensional matrix. The literature shows that the EPS possess significant properties such as renewable, biodegradable, eco-friendly, non-toxic, and economically valued product, representing it as a green alternative to the synthetic polymer. The cost-effective and green synthesis of the EPS must be encouraged by using agro-waste as a raw material. The main objective of the manuscript is to provide a comprehensive update on the various aspects pertaining to EPS, including the economic aspects of EPS production, provide an insight into the latest tools and techniques used for detailed structural EPS characterization along with updates in the integration of CRISPR/Cas9 technology for engineering the modification in EPS production, the role of newly discovered EPR3 as a signalling molecule in plant growth-promoting properties (PGP) or agricultural microbiology. Furthermore, the EPS achieved prospective interest prevailing potential environmental issues which can be subject to EPS treatment including, landfill leachate treatment, decolourization of dye from the effluent or waste generated by an industry, removal of radionuclides, heavy metals and toxic compounds from the various environments (aquatic and terrestrial), industry effluents, waste waters etc. are comprehensively discussed. Abstract : Bacterial exopolysaccharide; Engineering strategies; CRISPR; EPR3; Structural characterization; Biological activities; Environmental applications.